Recent Advancements and Therapeutic Applications of the Niosomal Drug Delivery System - Dandekar, Mayur R. (Asian Journal of Pharmaceutics (AJP), 2024)
Niosomes are a novel class of creative vesicular structures. They are made of biodegradable and essentially harmless non-ionic surfactants. They were created as more affordable and reliable alternatives to liposomes. Their function has expanded to include various application areas since they were first introduced to the cosmetics sector. They are currently being investigated as prospective medication delivery systems for focused and sustained delivery. They can be administered through ocular, transdermal, vaginal, and inhalation in addition to traditional, oral, and parenteral methods. Niosome delivery of biotechnological goods, like vaccines, is another fascinating and promising study topic. These systems have become even more relevant in developing a particular strategy in the form of proteasomes. Further, focused research efforts are still needed to fully exploit these innovative technologies. With a focus on their function in drug targeting, this review examines the current state and promise of niosomes in drug delivery. Their preparation techniques, formulation features, benefits, drawbacks, and applications are also described.